Photography and literature in Blow-Up by Julio Cortázar (Colloquia Comparativa Litterarum, 2025)
The article examines photography in Blow-Up by Julio Cortázar from the point of view of its representation, its functions, and its relationship to literature. While making use predominantly of close reading, the analysis also takes into account some reflections of the Argentinian author on the topics in question exposed elsewhere. A conclusion is reached that despite their distinct differences, photography and literature collaborate in the field of knowledge: they are both represented as means to reach the truth, as well as in the field of ethics: they both serve the moral engagement of the protagonist. Finally, the fantastic irruption of the character into the blow-up allows for aesthetic interpretations, as well.
Keywords: ekphrasis; photography; fantastic literature; Julio Cortázar; Blow-Up